EXPLORING THE LEGACY OF GREAT SCHOLARS IN CENTRAL ASIAN HISTORY.ECONOMIC DEVELOPMENT. DEVELOPMENT STRATEGIES OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Mo’minova Odina G’ulom qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: Central Asia, with its rich historical tapestry, has been home to numerous great scholars whose contributions have left an indelible mark on the region's intellectual and cultural landscape. This article delves into the lives and legacies of some of the most prominent scholars in Central Asian history, including al- Farabi, Ibn Sina, al-Biruni, Omar Khayyam, Mirzo Ulugbek, Al-Khwarizmi, Jalal ad- Din Rumi, Mahmud al-Kashgari, Ahmad Yasawi, Babur, Amir Timur, Al-Bukhari, and Alisher Navoi. Through an exploration of their works, achievements, and lasting influence, this article sheds light on the enduring legacy of these great minds and their contributions to knowledge, science, literature, and culture.